Rancang Bangun Biodigester Untuk Menghasilkan Biogas Berbahan Baku Limbah Sayur Kol dengan Campuran Rumen Sapi dan EM4 - Dhanu Fransgio Pratama Surya; Ferecia Fedora; Addin Akbar; Khairul Akli (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The large number of cattle breeders in Indonesia has positive and negative values. Cattle farmers generally produce livestock waste such as cow rumen. Cow rumen can be used as a starter for alternative biogas energy production, and cabbage vegetable waste has the potential to be used as raw material for making biogas, because it contains nutrients such as crude protein (PK) 22.47%, crude fat (LK) 3.05%, crude fiber (SK) 12.09%, dry matter 10.22% and extract material without nitrogen 34.96%. Apart from that, in this research cow rumen and EM4 were also used as starters for the anaerobic fermentation process. The cow's rumen contains methane bacteria, namely Methanosarcina sp, and the cow's rumen also contains quite high levels of organic compounds with a COD value of 17,183 mg/l. Effective Microorganisms (EM4) are bacteria whose function is to accelerate the degradation process of organic materials. The aim of this research is to design a biodigester, and carry out biodigester design trials. The research methods carried out are COD analysis, CH4 analysis and pH analysis. The results showed that the percentage of CH4 increased in a mixture of 100% cow rumen, because the total COD value in the substrate was directly proportional to the addition of the cow rumen composition. This can be seen from the total COD in 100% beef rumen starter of 1175 ppm.